2014
DOI: 10.1080/09168451.2014.932669
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Aeromonas hydrophila genes encoding the outer membrane receptor of ferrioxamine B and an AraC-type transcriptional regulator

Abstract: (2014) Identification and characterization of Aeromonas hydrophila genes encoding the outer membrane receptor of ferrioxamine B and an AraC-type transcriptional regulator, Bioscience, Biotechnology, and Biochemistry, 78

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The fact that orthologs exist in numerous Enterobacteriaceae hints that FoxR is likely to play a similar regulatory role in other bacteria. FoxR orthologs, designated DesR (regulator of DesA), have been reported in Aeromonas hydrophila and Vibrio vulnificus, two waterdwelling Gram-negative bacteria (Funahashi et al, 2014;Tanabe et al, 2005). DesR activates the transcription of desA (equivalent to foxA in S. Typhimurium, see Figure 1) by binding directly to its regulatory region, a process which is enhanced in the presence of nonphysiological concentrations of DFOB (1 mM), but not ferrioxamine B, the ironbound form of DFOB (Tanabe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that orthologs exist in numerous Enterobacteriaceae hints that FoxR is likely to play a similar regulatory role in other bacteria. FoxR orthologs, designated DesR (regulator of DesA), have been reported in Aeromonas hydrophila and Vibrio vulnificus, two waterdwelling Gram-negative bacteria (Funahashi et al, 2014;Tanabe et al, 2005). DesR activates the transcription of desA (equivalent to foxA in S. Typhimurium, see Figure 1) by binding directly to its regulatory region, a process which is enhanced in the presence of nonphysiological concentrations of DFOB (1 mM), but not ferrioxamine B, the ironbound form of DFOB (Tanabe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We have confirmed that Fur represses foxA and foxR expression in S. Typhimurium (Bjarnason et al, 2003;Teixidó et al, 2011;Tsolis et al, 1995) and identified potential Fur-binding sites in the foxR and foxA upstream regulatory regions. In V. vulnificus and A. hydrophila, desR and desA promoters were shown to harbor Furbinding sites using a Fur titration assay (Funahashi et al, 2014;Tanabe et al, 2005). Fur utilizes iron as a corepressor to negatively regulate genes involved in many aspects of iron acquisition when iron is plentiful (Bjarnason et al, 2003;Mey et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Neisseria gonorrhoeae , MpeR activates fetA , encoding the receptor of the enterobactin xenosiderophore [ 33 ]. Finally, DesR activates the transcription of desA, coding for the xenosiderophore ferrioxamine B receptor in Vibrio vulnificus and Vibrio furnissi [ 34 , 35 ] and Aeromonas hydrophila [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under iron-limiting conditions, Aer. hydrophila can regulate the expression of an outer membrane receptor encoded by the desA gene to acquire iron from the environment (Funahashi et al 2014). Therefore, desA is crucial for the survival and growth of Aer.…”
Section: Introductionmentioning
confidence: 99%